2020
DOI: 10.1089/thy.2020.0166
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Research in Thyroid Cancer: Challenges and Strategies for Improvement

Abstract: Until recently, thyroid cancer was one of the most rapidly increasing cancers in the United States. Disparities exist in many aspects of thyroid cancer care as a result of the multifactorial interplay of systemic, patient, and physician factors. To better understand the management of thyroid cancer in populations at risk for health disparities and subsequently implement changes that will lead to health equity for all patients with thyroid cancer, health services research with innovative approaches is necessary. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Women account for more than 75% of thyroid cancer cases. It is most frequently found in adults between the ages of 20 and 55 years (4)(5)(6). The frequency of this malignancy is believed to be between 1.2 and 2.4 per 100 000 individuals in Iran, and it is three times more common in women than in men (7).…”
Section: Introductionmentioning
confidence: 99%
“…Women account for more than 75% of thyroid cancer cases. It is most frequently found in adults between the ages of 20 and 55 years (4)(5)(6). The frequency of this malignancy is believed to be between 1.2 and 2.4 per 100 000 individuals in Iran, and it is three times more common in women than in men (7).…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in medical technology have led to the introduction of new devices that may potentially improve thyroid surgery outcomes patient safety. 15,16 Despite research conducted evaluating these devices compared with the conventional technique in thyroid surgery, there is still no consensus. The main reason for this is the conflicting results of the earlier research conducted in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities are present in thyroid conditions because of multiple systemic and patient factors [25]. The social and demographic traits of individuals, groups, and their communities have a great influence on the overall health of populations [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Black and Hispanic patients have lower diagnoses of thyroid disorders, higher complication and mortality rates, and increased hospital costs compared to white patients [28,31,32]. Racial and ethnic minorities are also more likely to be diagnosed with more advanced diseases, due to delayed presentation to a physician, and receive suboptimal treatment compared to non-Hispanic White patients [25].…”
Section: Introductionmentioning
confidence: 99%